Current Distribution of Selected Vector-Borne Diseases in Dogs in Spain - Montoya-Alonso, José Alberto; Morchón, Rodrigo; Costa-Rodríguez, Noelia; Matos, Jorge Isidoro; Falcón-Cordón, Yaiza; Carretón, Elena (Frontiers in Veterinary Science, 2020)
Currently, climate change, modifications of landscapes and habitats due to human activities, as well as an increase in the movement of reservoirs and new species of competent vectors, have contributed to the spread of canine vector-borne diseases. These are mostly emerging and neglected diseases, some of them with zoonotic potential. Therefore, the objective of this study was to assess the prevalence and distribution of four major canine vector-borne diseases (Dirofilaria immitis, Leishmania infantum, Anaplasma spp. and Ehrlichia canis) in Spain. Between September 2018 and February 2020, blood was sampled from 4643 client-owned dogs from 111 veterinary clinics from the 17 autonomous communities of Spain. All samples were tested for the detection of D. immitis antigens, and for antibodies against L. infantum, Anaplasma spp. and E. canis. Of the studied dogs, 22.14% were positive for one or several diseases while the prevalence was 6.25% (CI: 5.59-6.98) for D. immitis, and the seroprevalences were 10.36% (CI: 9.52-11.27) for L. infantum, 5.06% (CI: 4.47-5.73) for Anaplasma spp., and 4.26% (CI: 3.72-4.88) for E. canis. Co-infections by two and three vector-borne diseases were reported in 13% and 2% of the infected dogs, respectively. The studied vector-borne diseases are widely distributed throughout the Spanish geography, being observed and expanding northward in the case of D. immitis and L. infantum. The results point to an insufficiency of preventive measures to avoid the infection, and the need of the implementation of awareness campaigns among veterinarians and owners. Furthermore, a close collaboration between veterinarians, physicians and health authorities would be necessary for such zoonotic vector-borne diseases